2009
DOI: 10.1021/ic9013202
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth, Transport, and the Structural and Magnetic Properties of Ln4FeGa12 with Ln = Y, Tb, Dy, Ho, and Er

Abstract: Ln(4)FeGa(12), where Ln is Y, Tb, Dy, Ho, and Er, prepared by flux growth, crystallize with the cubic Y(4)PdGa(12) structure with the Im3m space group and with a = 8.5650(4), 8.5610(4), 8.5350(3), 8.5080(3), and 8.4760(3) A, respectively. The crystal structure consists of an iron-gallium octahedra and face-sharing rare-earth cuboctahedra of the Au(3)Cu type. Er(4)Fe(0.67)Ga(12) is iron-deficient, leading to a distortion of the octahedral and cuboctahedral environments due to the splitting of the Ga2 site into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…Because of their specific structure, intermetallic compounds usually exhibit unique physical and chemical properties that are potentially superior to their disordered alloy analogues and the pure metals. Such properties include, for example, magnetoresistance, superconductivity, enhanced catalytic activity, and hydrogen storage capability . Intermetallics and alloys containing Co or Ni and Sn with varying stoichiometry have mostly been studied as anode materials for Li‐ and Na‐ion batteries .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their specific structure, intermetallic compounds usually exhibit unique physical and chemical properties that are potentially superior to their disordered alloy analogues and the pure metals. Such properties include, for example, magnetoresistance, superconductivity, enhanced catalytic activity, and hydrogen storage capability . Intermetallics and alloys containing Co or Ni and Sn with varying stoichiometry have mostly been studied as anode materials for Li‐ and Na‐ion batteries .…”
Section: Introductionmentioning
confidence: 99%
“…The authors have previously reported a detailed discussion for the splitting of the Ga position in the isostructural LnMn x Ga 3 (Ln = Ho−Tm; x < 0.2)[7]. Similar splitting of a Ga site was used in Er 4 Fe 0.67 Ga 12 of the Y 4 PdGa 12 -structure type, where two gallium positions were observed on the unit cell faces[3].…”
mentioning
confidence: 94%
“…), respectively. Ln 4 MGa 12 (Ln = Tb−Er; M = Fe, Pd, and Pt) crystallizes in the Y 4 PdGa 12 -structure type and consists of facesharing LnGa 3 cuboctahedra with corner-sharing MGa 6 octahedra [3,4]. Ln 4 PtGa 12 (Ln = Dy−Er) exhibits large, positive magnetoresistance up to 50 %, 220 %, and 900 % increase in resistance under an applied magnetic field for Dy, Er, and Ho, respectively [4].…”
Section: Introductionmentioning
confidence: 99%
“…Single crystal X-ray diffraction analysis reveals that compound 1 exhibits the 2D pillar-layered coordination framework with meso-helical character constructed from auxiliary ligand TA 2− (that is, pillar) bridging two [Er(HIDC 2− )] n layers (namely, Δ-and Λ-layers), which is the first example of lanthanide coordination framework including imidazole-4,5-dicarboxlylate and terephthalate. Meanwhile, the thermogravimetric analysis shows compound 1 has high thermal stability.Rational design of novel metal-organic compounds has been attracting great interest from chemists in recent years [1][2][3], not only because of their intriguing variety of structures and topologies, but also because of their interesting potential of applications in functional solid materials, ion exchange, catalysis, optical electronic and magnetic devices [4][5][6][7]. At present, the research based on the assembly of metalorganic complexes from the single ligand imidazole-4, 5-dicarboxlylate or terephthalate has been extensively carried out [8][9][10][11][12].…”
mentioning
confidence: 99%
“…Rational design of novel metal-organic compounds has been attracting great interest from chemists in recent years [1][2][3], not only because of their intriguing variety of structures and topologies, but also because of their interesting potential of applications in functional solid materials, ion exchange, catalysis, optical electronic and magnetic devices [4][5][6][7]. At present, the research based on the assembly of metalorganic complexes from the single ligand imidazole-4, 5-dicarboxlylate or terephthalate has been extensively carried out [8][9][10][11][12].…”
mentioning
confidence: 99%